STRATEGI PEMASARAN TERHADAP PRODUK SIMPANAN PENDIDIKAN DI BMT RIZQONA IKABU DALAM PERSPEKTIF EKONOMI ISLAM - Zubaidah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This research aims to identify the marketing strategy of educational savings products implemented by BMT, its annual performance improvement, challenges in marketing the products, and the marketing strategies used by BMT Rizqona Ikabu. BMT Rizqona Ikabu adopts a marketing strategy based on the marketing mix components, namely Product, Price, Place, and Promotion. The product strategy includes educational savings products, general savings, and others, with pricing adjusted according to customers' capabilities. In terms of place strategy, BMT selects easily accessible locations for customers and potential clients. Meanwhile, the promotion strategy involves conducting educational programs, providing excellent services, expanding cooperation with other parties, and advertising through distributing brochures. The research findings conclude that BMT Rizqona Ikabu implements a marketing strategy using the marketing mix approach, which includes Product, Price, Place, and Promotion. The marketing strategy focuses on providing educational savings, general savings, and other products with pricing tailored to the customers' capabilities. For the place strategy, BMT selects easily accessible locations for customers and potential clients. Additionally, the promotion strategy involves efforts to clarify intentions, provide excellent service, expand cooperation networks, and use advertising methods such as distributing brochures. The research findings also conclude that the marketing strategy applied by BMT Rizqona Ikabu aligns with the principles and values of Islamic Economics, namely justice (Adl) and mutual cooperation (Takaful).